Pengaruh Perbandingan Komposisi Ampas Tebu dan Kulit Durian Terhadap Karakteristik Bio-oil - Iriany; Maulisa; Salsabila; Taslim (Jurnal Teknik Kimia USU, 2025)
The bio-oil from bagasse has poor physical characteristics, so it requires a combination with other materials, such as durian peel. This study aims to produce high-quality bio-oil from the best composition ratio of bagasse and durian peel. The study used variations of sugarcane bagasse and durian peel compositions (0:1; 1:0; 1:1; 2:1; 3:1) at a pyrolysis temperature of 400 °C for 5, 6, and 7 hours using an 83.1 L upright cylindrical reactor. The bio-oil with the best characteristics was found at a 1:1 ratio, with yields of 32.28%, 38.82%, and 40.8%, pH values of 2.7; 2.8; 2.9, and viscosities of 0.952 cSt, 0.928 cSt, and 0.908 cSt. The results show that adding durian peel improves the bio-oil characteristics.